Effects of a modular teacher coaching program on child attention problems and disruptive behavior and on teachers' self-efficacy and stress. (December 2020) - Hanisch, Charlotte; Eichelberger, Ilka; Richard, Stefanie; Doepfner, Manfred
Symptoms of attention-deficit/hyperactivity and oppositional defiant disorder are associated with a multitude of psychosocial developmental risks, e.g. academic underachievement. Various cognitive behavioral interventions have proven to be effective in reducing problem behavior in school settings. Drawing on this previous work and on our parent-focused preventive and therapeutic programs, we developed the school-based coaching for elementary school teachers of children with attention deficits or disruptive behavior problems (SCEP). Based on functional behavior assessment, SCEP addresses teachers of children with severe externalizing behavior problems in an individualized modular manner. It consists of a one-day training course and fortnightly one-to-one or team-coaching sessions. We analyzed the effects of SCEP in a within-subject control group design ( N = 60), with student attention problems and rule-breaking behavior during class as the primary outcome measure. SCEP was found to reduce problem behavior during lessons, with small to medium effect sizes ( d = 0.42–0.6). After the intervention, teachers reported changes in their use of praise and felt more confident managing the class ( d = 0.58). The results of SCEP are discussed in light of multi-tiered preventive approaches that suggest extensive individualized interventions based on functional behavior analysis for children with severe problem behavior.